2016
DOI: 10.1038/srep31889
|View full text |Cite
|
Sign up to set email alerts
|

CaM/BAG5/Hsc70 signaling complex dynamically regulates leaf senescence

Abstract: Calcium signaling plays an essential role in plant cell physiology, and chaperone-mediated protein folding directly regulates plant programmed cell death. The Arabidopsis thaliana protein AtBAG5 (Bcl-2-associated athanogene 5) is unique in that it contains both a BAG domain capable of binding Hsc70 (Heat shock cognate protein 70) and a characteristic IQ motif that is specific for Ca2+-free CaM (Calmodulin) binding and hence acts as a hub linking calcium signaling and the chaperone system. Here, we determined c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 55 publications
3
67
0
Order By: Relevance
“…Their precise molecular role(s) during these processes are not clear yet, but their mitochondrial localization is likely crucial for their biological function, since TTM1 DTM, which does not localize to the mitochondria, lost its ability to complement the ttm1 mutant phenotype. The involvement of mitochondria in plant PCD has been suggested but is not understood well (Lam et al, 2001;Qamar et al, 2015;Li et al, 2016). Based on the presence of the C-terminal transmembrane domains ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Their precise molecular role(s) during these processes are not clear yet, but their mitochondrial localization is likely crucial for their biological function, since TTM1 DTM, which does not localize to the mitochondria, lost its ability to complement the ttm1 mutant phenotype. The involvement of mitochondria in plant PCD has been suggested but is not understood well (Lam et al, 2001;Qamar et al, 2015;Li et al, 2016). Based on the presence of the C-terminal transmembrane domains ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous genes have been reported to be differentially expressed during the leaf senescence process [44], and many SAGs have been verified to be involved in leaf senescence [33,34,[45][46][47][48][49]. The detected SAGs of PIFs (PIF3, PIF34, and PIF35), SENs (SEN1 and SEN4), transcription factors (TFs; WRKY6, NAC2, and NAP), and cell death-related genes (PDCD5 and ACD1), showed significant abundant accumulation in the Arabidopsis ao1-1 mutant (Figure 8, Supplementary Figure S1), indicating that the function of AO is closely associated with the expression of these genes.…”
Section: Functional Role Of Ao Genes In Response To Light Regulationmentioning
confidence: 99%
“…This feature is intriguing given the role of the mitochondria in intrinsic apoptosis pathways and that none of the animal BAGs are localized to the mitochondria. Li et al (101) recently suggested that AtBAG5 forms a complex with Hsc70 and CaM that regulates plant senescence. AtBAG6 is the largest member of this family and was originally identified as a CaMbinding protein (88).…”
Section: The Emerging Role Of Plant Bag Proteins In Cell Death Regulamentioning
confidence: 99%